Analisis Kebutuhan Pengembangan Bahan Ajar pada Konsep Interaksi Antarmolekul dan Printer Inkjet - Nina Adriani; Inelda Yulita; Amin Fatoni; Dadan Hermawan; Ahmad Mudzakir (SAP (Susunan Artikel Pendidikan), 2021)
The link between learning materials and the surrounding known as scientific literacy is an important thing for educators to do today. Scientific literacy is needed and it continues to be developed, especially in developing teaching materials. This research is conducted to know the needs of prospective teachers for developing teaching materials on intermolecular interactions and its connection with the concept of an inkjet printer. This analysis used an interview worksheet and conceptual questions given to chemistry learning students to discover the correlation between the material and the relationship with the existing context. The outcomes of the worksheet data were constructed using descriptive qualitative methods. The results stated that 97% of students already knew and were familiar with inkjet printers, but only 49% understood how the cognition of intermolecular interaction material in the circumstance of inkjet printers. 83% of students stated that there was a relationship between chemical materials and inkjet printers, but only 11% understood how the interactions between ink and paper were related in terms of chemical bonds. Students also stated that 89% required the use of teaching materials that linked the concept of interactions between molecules and their relationship with the context of an inkjet printer. Therefore, according to the conclusion of this research, teaching material is going to be developed that can explain the connection between the concepts of molecular interaction and the context of an inkjet printer to the prospective chemistry teachers.